Accounting Knowledge, Internal Locus of Control, Digital Literacy, and Adversity Intelligence: Influences on Accounting Students' Entrepreneurial Intentions - Permana, I Kadek Ega Prastha; Suryanawa, I Ketut; Sudirga, I Gusti Ayu Desni Saraswati (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
Entrepreneurial intention refers to the desire and determination to establish, manage, bear the risks of, and grow a business. This research investigates the influence of accounting knowledge, internal locus of control, digital literacy, and adversity intelligence on the entrepreneurial intentions of accounting students. The study population comprised all undergraduate accounting students from the 2017 to 2023 cohorts at the Faculty of Economics and Business, Udayana University. A sample of 300 students was selected using the probability sampling method with a proportionate stratified random sampling technique. The data collected through questionnaires were analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) program. The findings reveal that accounting knowledge, internal locus of control, digital literacy, and adversity intelligence positively and significantly affect the entrepreneurial intentions of accounting students. Keywords: Entrepreneurial Intentions; Accounting Knowledge; Internal Locus of Control; Digital Literacy; Adversity Intelligence